The Relationship of a Foreign Tour Operator in Serbia towards Tourists Based on the Example of TUI - Marija Šuleić (Turizam, 2015)
Tourism represents a widespread phenomenon in which around a billion of people participates, so that it is understandable that a small percentage of the dissatisfied represents a serious contingent. Therefore the complaints of the users of travel agencies’ services arise. In order to protect itself, each responsible company must undertake a package of various measures, aiming at increasing the quality of providing services, in other words, increasing its competitiveness. EU tourists are protected in large measure by the regulations associated with consumers’ protection because different travel guidelines have been introduced. Serbia is also on the way of the adoption of all measures. The aim of this research was to analyze which mechanisms are used by TUI in order that tourists be satisfied with their purchased arrangements and which approach TUI applies in Serbia for solving possible complaints of end-users of its services. The research results can be useful not only for travel agencies, but for tourists as well.